Hadith (Beware of green dung beetles) A critical analytical study (Journal of the College of Basic Education, 2026)
Many hadiths have become popular among people and have influenced them through their application and adherence to their meanings. Despite the fact that they are weak hadiths, even fabricated ones, people have not paid attention to them in this regard. Therefore, it is necessary to point out their rulings in terms of acceptance and rejection...and also the extent to which people are affected by these hadiths, including the hadith “Beware of the green dung beetle,” which I will study analytically and critically. I will explain in my study the hadith topics that take it from the realm of ignorance to the realm of knowledge.